Phenomenon of intellectual entrepreneurship and emerging patterns of intellectual entrepreneurship in Latvia - Sennikova, Irina; Kurovs, Boriss (Journal of Business Economics and Management, 2006)
The paper is a report on the work in progress on the broader exploratory study into intellectual entrepreneurship in the Baltics, which aims to explore the emerging patterns of intellectual entrepreneurship through experience of individuals. The findings are based on the qualitative interviews with 13 entrepreneurs, who fit Johansson et. al. (1999) and Konstantinov and Filonovich (2005) definition of intellectual entrepreneurs and whose businesses fit Schumpeter's (1934) definition of innovativeness. Based on the literature of intellectual entrepreneurship the emerging typology of intellectual entrepreneurship was developed to assist in selecting the sample. The participants of the study were divided into the following categories: entrepreneuring academics, entrepreneuring academic profesionals, entrepreneuring intellectuals and intuitive entrepreneurs. During the study three emerging patterns of IE in Latvia were identified, which can be called ‘an ideal one’, ‘professional one’ and a ‘forced one’ depending on the educational, professional and experiential background of the entrepreneurs. The identified patterns will lay the foundation for further development of training and educational programmes for potential entrepreneurs, providing specialised cross‐disciplined programmes not only for students studying entrepreneurship, economics or business, but also for the students from other disciplines, thus increasing the potential for developing intellectual entrepreneurs. It will also allow identifying the ways of utilising intellectual capacity of individuals and attracting them into entrepreneurship in non‐extreme, positive circumstances.Firstd Published Online: 14 Oct 2010